Spectral Analysis of the Dependence of Labor Force Participation on Unemployment and Wages - Goodman, John L. (The Review of Economics and Statistics, 1974)
of the two major specifications of the Phillips curve supports the view of the expectations approach to the theory of inflation. In both specifications of the Phillips curve, evidence of a distributed lag between the variables was uncovered. Of particular interest are the findings that (1) unemployment lags wage changes and the lag is distributed, (2) wages lag prices, and (3) the level of profits are only weakly related to the rate of change in money wages.